Comprehensive Review of Teamwork and Coordination between Nursing and Emergency Staff in High-Stress Situations - Alyami , Sami Nasser Misfer; Alyami , Mahdi Salem Ali; Al-Khadrah , Saleh Rashid S; Al Makhalas , Shohra Mohammed S; Al Mutleq , Nouf Mansour M; Alsharari , Nawaf Thaqil; Alsharari , khalid Olayan M; Alyami , Ali Mohammed M; Lsloom , Hamad Saleh A; Lasloom , Jaber Saleh A; Alsallum , Salem Nasser M; Lesloom , Mersal Mahdi A; et al. (Journal of Ecohumanism, 2024)
Due to specialized roles and highly stressful practice areas such as emergency department and disaster response, there must be cooperation between nursing and emergency staff. Specifically, critical care requires high-quality teamwork, time-sharing, and rational management of all available resources to provide patients with the required care. This review delves into the challenges of teamwork, which comprises inclusiveness of communication issues, role definition disparities, and scarcity of resources for implementing teamwork strategies, including simulation training, leadership advancement, and the use of standardized communication protocols such as SBAR (Situation, Background, Assessment, Recommendation). The study reveals that improvements in team cooperation have important implications for increases in the safety of patients and a decrease in errors among emergency care providers. Suggestions for enhancing team processes and organizational facilitative structures are made.